Early diagnosis of gastric cancer - Sojo-Durán, Enrique (Cirugía del Uruguay, 1973)
In Japan great progress has been achieved in the early diagnosis of gastric cancer. The procedure employed is Endoscopy performed by fiberscope, which permits vi,sualization of complete gastric mucosa, biopsies and citologic lavage or study by smear of biopsed piece. The method most employed is the latter.